Consultas planteadas al ICAC - García Giménez, Pilar; Ayats Vilanova, Anna; Romano Aparicio, Javier (Revista de Contabilidad y Tributación. CEF, 2002)
BOICAC núm. 45, 03-2001. Consulta 2. BOICAC núm. 46, 06-2001. Consulta 1. BOICAC núm. 37, 03-1999. Consulta 3.